An Overview on Marek’s Disease Virus Evolution and Evidence for Increased Virulence in Brazil - Torres,ACD (2019)
ABSTRACT Marek’s disease virus (MDV) has been shown to be evolving to higher virulence. One of the genetic sites involved in virulence which enables such characterization is the 339-amino acid Meq protein encoding gene (meq). The reemergence of clinical Marek’s disease (MD) in vaccinated flocks can be associated to changes in meq. Our studies have shown the presence of very virulent MDV strains in the Brazilian industrial and free-range poultry. We present an overview of MD increasing severity and indicate the necessity of using phylogenetic tools for best accompanying MDV evolution.